Runaway Social Selection in Human Evolution - Crespi, Bernard J.; Flinn, Mark V.; Summers, Kyle (Frontiers in Ecology and Evolution, 2022)
Darwin posited that social competition among conspecifics could be a powerful selective pressure. Alexander proposed a model of human evolution involving a runaway process of social competition based on Darwin’s insight. Here we briefly review Alexander’s logic, and then expand upon his model by elucidating six core arenas of social selection that involve runaway, positive-feedback processes, and that were likely involved in the evolution of the remarkable combination of adaptations in humans. We discuss how these ideas fit with the hypothesis that a key life history innovation that opened the door to runaway social selection, and cumulative culture, during hominin evolution was increased cooperation among individuals in small fission-fusion groups.